STRATEGI PENGELOLAAN SAMPAH 3R DI DESA TRAWAS KECAMATAN TRAWAS KABUPATEN MOJOKERTO - Nur Michmidatin; Isnaini Rodiyah (Journal Publicuho, 2024)
The 3R waste management strategy (Reduce, Reuse, Recycle) is a government effort to deal with existing waste problems, with the main objective of minimizing the amount of waste entering the Final Disposal Site (TPA). This study analyzes the implementation of 3R waste management at the TPS in Trawas Village, Trawas District, Sidoarjo Regency. With a descriptive and qualitative approach, this study aims to analyze and describe the 3R waste management strategy through objectives, environment, direction, action, and learning. The research method includes interview sessions (related to sources), observation, documentation, and literature studies or literature reviews, with data analyzed using the Miles and Huberman analysis model. The findings of this study indicate that the 3R waste management strategy in Trawas Village, seen from the Objective factor, requires the addition of more complete facilities and infrastructure so that the waste management process can run optimally. From the Environmental factor, both internal and external, all parties have been involved and have an important role in running this 3R program. From the direction factor, more intensive education and socialization are needed so that the community can better understand the waste management process. From the action factor, the coordination carried out is running effectively. From the learning factor, the evaluation and monitoring that have been carried out have been running to assess the success of the 3R program.